WEB-BASED COOPERATIVE LEARNING, LEARNING STYLES, AND STUDENT’S LEARNING OUTCOMES - Bambang Hariadi (LPMPP Universitas Negeri Yogyakarta, 2015)
Abstract: This study was aimed to examine the effect of the instructional learning strategy (webbased STAD-type cooperative and text-based STAD-type cooperative learning strategies) and learning styles towards student learning achievement. This quasi-experimental study used a non-equivalent control group version of the factorial design. The subjects were the first-semester undergraduate students of Information Systems at STIKOM Surabaya. Sixty-nine (69) students were involved, 34 of whom were the subjects of the experimental group and 35 were the subjects of the control group. The collected data were statistically analyzed by using the two-way analysis of variance technique (ANOVA) with the significance level of 0.05. The findings of this research indicate that there was a significant difference in learning achievement, for the General Management course, between groups of students taught with the web-based STAD-type cooperative learning strategies and those taught with the text-based STAD-type cooperative learning strategies. Based on the findings, the researcher suggests lecturers to implement the STAD-type cooperative learning strategies, and use the web-based and text-based strategies simultaneously (complementarily) in the form of blended learning. Keywords: learning strategy, STAD type cooperative, web based learning, learning styles, learning outcomes PEMBELAJARAN KOOPERATIF BERBASIS WEB, GAYA BELAJAR, DAN HASIL BELAJAR MAHASISWA Abstrak: Penelitian ini bertujuan untuk menguji pengaruh strategi pembelajaran (kooperatif tipe STAD berbasis web vs kooperatif tipe STAD berbasis teks) dan gaya belajar terhadap hasil belajar mahasiswa. Penelitian kuasi eksperimen ini menggunakan desain faktorial versi nonequivalen control group design. Subjek penelitian ini adalah mahasiswa program studi Sistem Informasi semester I di STIKOM Surabaya yang berjumlah 69 mahasiswa, terdiri dari 34 mahasiswa untuk kelas eksperimen dan 35 mahasiswa untuk kelas kontrol. Data yang terkumpul diolah secara statistik dengan menggunakan teknik analisis varian dua jalur dengan menggunakan taraf signifikansi 0,05. Hasil penelitian ini menunjukkan bahwa terdapat perbedaan hasil belajar mata kuliah Manajemen Umum yang signifikan antara kelompok mahasiswa yang dibelajarkan dengan strategi kooperatif tipe STAD berbasis web dan strategi kooperatif tipe STAD berbasis teks. Berdasarkan temuan penelitian ini disarankan untuk menerapkan strategi pembelajaran kooperatif tipe STAD dan menggunakannya secara bersamaan (saling melengkapi) antara yang berbasis web dengan yang berbasis teks dalam bentuk blended learning. Kata Kunci: strategi pembelajaran, kooperatif tipe STAD, web base learning, gaya belajar, hasil belajar